Implementasi Sistem Monitoring HVAC Ruang Server menggunakan Raspberry Pi Berbasis Web (Studi Kasus pada PT Rahajasa Media Internet Surabaya) - Najih Razzaaq Nur Azhiim (Jurnal Jaringan Telekomunikasi, 2019)
The server room is a room that contains the server computer installation or where the main equipment for the server computer is placed. Lack of supervision and monitoring from employee server room conditions is one of the factors causing damage to existing devices. Therefore a monitoring system was created to monitor the server room periodically using web to make it easier for employees to monitor the server room. The system will automatically send notification to telegram when the temperature or dust particles exceed the specified range. The purpose of this study was to test the hvac monitoring system in server room, test the temperature and dust readings on the server room hvac monitoring system, know and calculate the value of the suitability and accuracy of the server room hvac monitoring tool, and to test the QoS of web server on monitoring the server room hvac. The result is the system able to read the server room temperature in range 18°C - 27°C, can read the increase in dust particles when there's activity in the server room up to the range 0cf - 1500cf and when in normal conditions it reads up to the range 0cf-1000cf, For the sensor accuracy, the total error rate is 0.79%, and QoS when using a LAN connection get the largest delay 410.084ms, the biggest throughput is 601bits/s, and the highest packet loss is 0.16%, while when using wifi connection the biggest delay is 410.608ms., the largest throughput 647 bits/s, and the highest packet loss 0.12%.